2019
DOI: 10.1111/ajad.12869
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Micro‐Induction of Buprenorphine/Naloxone for Opioid Use Disorder in an Inpatient Setting: A Case Series

Abstract: Background and ObjectivesBuprenorphine/naloxone has been shown to be effective in the treatment of opioid use disorder. Due to its pharmacological properties, induction can be challenging, time‐consuming, and result in sudden onset of withdrawal symptoms.MethodsRetrospective case series (n = 2).ResultsTwo patients with opioid use disorder were successfully started on buprenorphine/naloxone using a rapid micro‐induction technique that did not cause precipitated withdrawal or require preceding cessation of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 16 publications
6
112
0
Order By: Relevance
“…8,19 In a 2016 publication, the authors described two patients whose transitions lasted between 9 and 29 days in the outpatient setting, the first switching from street heroin and the second switching from methadone and diacetylmorphine (pharmaceutical heroin). 8 In the hospital setting, another study 12 described two patients who required surgery for various complications related to their admission diagnoses, both of whom were transitioned from hydromorphone. The first patient started with a dose of 0.25 mg sublingual buprenorphine and took 5 days to transition fully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,19 In a 2016 publication, the authors described two patients whose transitions lasted between 9 and 29 days in the outpatient setting, the first switching from street heroin and the second switching from methadone and diacetylmorphine (pharmaceutical heroin). 8 In the hospital setting, another study 12 described two patients who required surgery for various complications related to their admission diagnoses, both of whom were transitioned from hydromorphone. The first patient started with a dose of 0.25 mg sublingual buprenorphine and took 5 days to transition fully.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] The dose is gradually increased until it occupies a substantial portion of opioid receptors, and the full opioid agonist is then discontinued. Buprenorphine microdosing was used in both the inpatient and outpatient settings to transition from various full l-opioid agonists, 8,[12][13][14] with durations ranging from 3 12 to 29 8 days, and with various adjunctive enhancements such as transdermal buprenorphine 15,16 and fentanyl. 13,17 Several examples of protocols are listed in Appendix 1.…”
mentioning
confidence: 99%
“…A factor in the increased potency of fentanyl and other synthetic opioids is their higher binding affinity in comparison to prescription opioids like oxycodone, possibly contributing to the potential need for higher doses of buprenorphine/naloxone . As a result of the change in drug landscape clinicians have been employing new strategies to help patients including non‐traditional and rapid induction protocols among other strategies . The case under discussion highlights this shift in drug patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Patients have consistently reported that the induction process is well tolerated, with a reduction or elimination of cravings and avoidance of precipitated withdrawal. 4,5 Although further research evaluating "microdosing" with buprenorphinenaloxone is certainly needed (we found only 2 case reports and 1 small case series), 4,5 adoption of this prescribing approach may offer a safe and effective alternative strategy for buprenorphine-naloxone induction among patients with an opioid use disorder. In the wake of an ever-changing illicit drug market, innovation (with simultaneous evaluation) is needed to help turn the tide on North America's opioid crisis.…”
mentioning
confidence: 98%